2D molybdenum nitride nanosheets as anode materials for improved lithium storage. Issue 40 (10th October 2018) - Wang, Liangbiao; Zhang, Kailong; Pan, Honglin; Wang, Li; Wang, Di; Dai, Weicheng; Qin, Hengfei; Li, Gaoran; Zhang, Junhao
Abstract : Two-dimensional (2D) molybdenum nitride (MoN) nanosheets are promising anode materials for improved lithium-ion batteries. Abstract : Two-dimensional (2D) molybdenum nitride (MoN) nanosheets are promising anode materials for improved lithium-ion batteries. However, the reported synthesis methods of MoN generally rely on high-temperature and complex procedures with low cost efficiency. Herein, we report a facile one-pot synthesis of 2D MoN nanosheets at a low temperature of 400 °C via a solid-state reaction of molybdenum disulfide, sulfur and sodium amide in an autoclave. When employed as the anode material for lithium ion batteries, the as-developed MoN electrode exhibits outstanding cyclability with a high capacity retention of 898 mA h g −1 over 400 cycles at a current rate of 200 mA g −1 as well as a superb rate capability with a capacity of 505 mA h g −1 at a high rate up to 2 A g −1 . The excellent lithium storage performance of the MoN electrode is attributed to its advantageously high conductivity and unique 2D nanostructure.